AKT isoforms modulate Th1‐like Treg generation and function in human autoimmune disease. (16th June 2016) - Kitz, Alexandra; de Marcken, Marine; Gautron, Anne‐Sophie; Mitrovic, Mitja; Hafler, David A; Dominguez‐Villar, Margarita
Abstract: Foxp3 + regulatory T cells (Tregs) exhibit plasticity, which dictates their function. Secretion of the inflammatory cytokine IFNγ, together with the acquisition of a T helper 1 (Th1)‐like effector phenotype as observed in cancer, infection, and autoimmune diseases, is associated with loss of Treg suppressor function through an unknown mechanism. Here, we describe the signaling events driving the generation of human Th1‐Tregs. Using a genome‐wide gene expression approach and pathway analysis, we identify the PI3K/AKT/Foxo1/3 signaling cascade as the major pathway involved in IFNγ secretion by human Tregs. Furthermore, we describe the opposing roles of AKT isoforms in Th1‐Treg generation ex vivo . Finally, we employ multiple sclerosis as an in vivo model with increased but functionally defective Th1‐Tregs. We show that the PI3K/AKT/Foxo1/3 pathway is activated in ex vivo ‐isolated Tregs from untreated relapsing–remitting MS patients and that blockade of the pathway inhibits IFNγ secretion and restores the immune suppressive function of Tregs. These data define a fundamental pathway regulating the function of human Tregs and suggest a novel treatment paradigm for autoimmune diseases. Synopsis: This study reveals the major signaling pathways involved in the generation of T helper 1 (Th1)‐like Tregs and the differential roles of AKT isoforms in modulating the Th1‐Treg phenotype. The PI3K/AKT/Foxo1/3 signaling cascade is the major pathway involved in IFNγ secretion by human Tregs. The different AKT isoforms have non‐overlapping roles in Th1‐Treg generation. Tregs isolated ex vivo from MS patients show activation of the PI3K/AKT/Foxo1/3 pathway and its modulation restores their normal phenotype and function. Abstract : This study reveals the major signaling pathways involved in the generation of T helper 1 (Th1)‐like Tregs and the differential roles of AKT isoforms in modulating the Th1‐Treg phenotype.